Efek Iradiasi Sinar Gama Terhadap Perkecambahan, Pertumbuhan, dan Parameter Biokimia Sengon (Falcataria falcata) - Kusuma, Fitria Dewi; Supriyanto, Supriyanto; Soekarno, Bonny PW; Ashari, Reyna (Savana Cendana, 2024)
Gamma-ray irradiation on plant seeds can affect plants’ growth and biochemical content. The application of gamma-ray irradiation can improve the quality of plants. This research aims to investigate the effect of gamma irradiation on the germination, growth, and chlorophyll content of sengon. Sengon seeds were irradiated with gamma rays at 0 (control), 25, 75, 125, and 175 Gy dose. Sengon seeds germinated and rared for four months. The study used a one-factor, completely randomized design (CRD). The parameters observed were the germination percentage, seedling height, diameter, and chlorophyll content. The result showed that gamma irradiation treatment can increase seed germination. Seeds irradiated with a dose of 75 Gy had a higher germination percentage than the other doses. Gamma irradiation with a dose of 25-175 Gy had of height and diameter of the seedlings compared to the control. Seedlings irradiated with a dose of 125 Gy had a higher chlorophyll content than other doses. Seedlings irradiated with a dose of 75 Gy had lower chlorophyll content than other doses. Therefore, in further experiment dose of gamma irradiation 25-175 Gy can be used to improve seeds’ viability. To increase the height and diameter of the seedlings, further research is still needed to investigate the effect of other doses on the growth of the seedlings.